Combination of Acupoints for Alzheimer’s Disease: An Association Rule Analysis - Wang, Yao-Chin; Wu, Chieh-Chen; Huang, Abel Po-Hao; Hsieh, Po-Chun; Kung, Woon-Man (Frontiers in Neuroscience, 2022)
Background Alzheimer's disease (AD) is an ongoing neurological degeneration characterized by amnesia and a decline in cognitive abilities. Hippocampal neurogenesis is the leading cause of Alzheimer’s disease. Mild cognitive impairment, a prodromal state of AD, is mainly due to the degradation of neuropsychiatric manifestations. Previous systematic reviews demonstrated that treatment with acupuncture with Chinese herbs is tolerable and effective in improving cognitive function in patients with AD. Our investigation aimed to discover the main acupoint combination for AD management based on a preceding systematic review and meta-analysis of randomized control trials (RCTs). Methods Our investigation was executed using association rule analysis, which is a common data mining technique accessible within R. Our study elucidated acupoint locations as binary data from 15 of the included studies using the Apriori algorithm. Results Thirty-two acupoints were selected from 15 RCTs. The 10 most frequent acupoints were selected. We inspected 503 association rules using the interpreted acupuncture data. The obtained results showed that {SP6, BI10} => HT7 and {HT7, BI10} => SP6 were the most associated rules in 15 RCTs. Conclusion The combination of acupoints ({SP6, BI10} => HT7 and {HT7, BI10} => SP6) can be acknowledged as a core combination for future acupuncture regimens of AD.